International Partnerships in Educational Institutions and their Intricacies: Are Institutions getting the right “deal” in the Partnerships? - Kaguhangire-Barifaijo, Maria; Namara, Rose. B. (Uganda Management Institute, 2012)
International partnerships have become an interactive response to the impacts of globalization and global changes. Today, higher institutions of learning establish alliances to be able to compete for funds, students, researchers as well as academic programmes. These partnership initiatives are believed to strengthen quality of academic programmes, build capacity and strengthen institutional profiling; increase potential for research capacity, and improve the impact of research on policy and practice within diverse contexts. While it seems clear that international partnerships are inevitable, intricacies in agreements and deep inequalities undergird many of the current trends in these partnerships. The questions this paper attempts to answer in relation to international partnerships are; first, how do power-relations affect international partnerships? Second, are these international partnerships truly building institutional capacity? The authors adopted the “Critical Theory Approach” to explain the inherent inequalities which affect harmony, cohesion, success and sustainable relationships. This paper asserts that unequal power relations remains a challenge in international collaborations in education institutions and the more powerful partners dominate the direction of the partnership, although international partnerships remain critical in building institutional capacity. The paper concludes that lack of clear agreements have an impact on the sustainability of partnerships. Hence, institutions need to be vigilant to negotiate the powers that enhance harmony through formal and transparent agreements and bring everyone on board to avoid institutional conflicts.
Keywords: Collaborations; Critical theory approach; Educational institution; Higher education; Agreements; International partnerships; Globalization; Linkages; Power relations; Researches; Sustainability; Universities